Demonstration of surface-enhanced Raman scattering by tunable, plasmonic gallium nanoparticles - Wu, Pae C (2009)
[Image: see text] Size-controlled gallium nanoparticles deposited on sapphire are explored as alternative substrates to enhance Raman spectral signatures. Gallium’s resilience following oxidation is inherently advantageous compared to silver for practical ex vacuo, non-solution applications. Ga nanoparticles are grown using a simple, molecular beam epitaxy-based fabrication protocol, and by monitoring their corresponding surface plasmon resonance energy through in situ spectroscopic ellipsometry, the nanoparticles are easily controlled for size. Raman spectroscopy performed on cresyl fast violet (CFV) deposited on substrates of differing mean nanoparticle size represents the first demonstration of enhanced Raman signals from reproducibly tunable self-assembled Ga nanoparticles. Non-optimized aggregate enhancement factors of ~80 were observed from the substrate with the smallest Ga nanoparticles for CFV dye solutions down to a dilution of 10 ppm.